2018
DOI: 10.1177/0022034518803095
|View full text |Cite
|
Sign up to set email alerts
|

Shh Plays an Inhibitory Role in Cusp Patterning by Regulation of Sostdc1

Abstract: Crown shapes in mammalian teeth vary considerably from species to species, and morphological characters in crown shape have been used to identify species. Cusp pattern is one of the characters in crown shape. In the processes governing the formation of cusp pattern, the Shh pathway has been implicated as an important player. Suppression of Shh signaling activity in vitro in explant assays appears to induce supernumerary cusp formation in wild-type tooth germs. However, the in vivo role of Shh signaling in cusp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 32 publications
1
26
0
Order By: Relevance
“…These defects extended to the dentition where Shh GFP/GFP mice have fusion between M1 and M2 but no supernumerary teeth (Fig. 7A, B) (Cho et al, 2011; Kim et al, 2019). The loss of a single Gas1 allele did not affect the underlying molar phenotype in either a Shh GFP heterozygous or homozygous background (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…These defects extended to the dentition where Shh GFP/GFP mice have fusion between M1 and M2 but no supernumerary teeth (Fig. 7A, B) (Cho et al, 2011; Kim et al, 2019). The loss of a single Gas1 allele did not affect the underlying molar phenotype in either a Shh GFP heterozygous or homozygous background (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Shh has been shown to restrict cusp formation by regulating the spacing between cusps within individual teeth (Cho et al, 2011; Harjunmaa et al, 2012; Harjunmaa et al, 2014; Kim et al, 2019) and is also required for appropriate spatial patterning between teeth within the molar dentition (Cho et al, 2011). Specifically, a negative feedback reaction-diffusion model has been identified with Wnt signalling activating Shh in the enamel knot; which in turn, activates the Wnt-inhibitor Wise in surrounding mesenchyme (Cho et al, 2011; Kim et al, 2019). The effects of Shh inhibition on cusp patterning have been investigated in embryos following maternal administration of the Shh blocking antibody 5E1.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Down-regulation of Axin2 both in the inhibitor and mimic treated specimen suggested that Axin2 functions autonomously in treated tissues not working as a negative feedback regulator of Wnt signaling. Further, the levels of Fgf4 and Shh , two important signaling factors for tooth development [ 46 , 47 ], were altered in the EK and IEE, presumably contributing to the altered morphogenesis of EK and overall tooth structure. These results suggested that miR-206-3p regulated tooth development through the Wnt, Bmp, and Shh signaling pathways.…”
Section: Discussionmentioning
confidence: 99%